Behavioral Investments in the Short Term Fail to Produce a Sunk Cost Effect. Issue 5 (October 2019) - Nash, Jeremy S.; Imuta, Kana; Nielsen, Mark
A cognitive bias known as the sunk cost effect has been found across a number of contexts. This bias drives the continued investment of time, effort, or money into an endeavor on the basis of prior investments into it. In Studies 1 and 2, we attempted to observe whether this effect occurs for short-term behavioral investments. In both studies, a reverse, or no sunk cost effect was found. In Study 3, we attempted to find an effect using hypothetical scenarios that were analagous to the behavioral investments presented in Study 1. This also failed to reveal an effect. Finally, Study 4 was an attempt to replicate a previously used hypothetical investment scenario; with results this time revealing the effect. A number of explanations for this pattern of results, such as participation and salient physical exertion, are discussed, with the possibility that some short-term behavioral investments are not subject to the sunk cost effect.